Bioaccumulation of trace elements by Leach's storm-petrels (Hydrobates leucorhous) in the North and South Atlantic Ocean during the non-breeding period - Catherine Potvin; Manon Sorais; Robert A. Ronconi; Katharine R. Studholme; April Hedd; Alexander L. Bond; Vegard S. Bråthen; Sydney M. Collins; Laura Crick; Joshua T. Cunningham; Anne N.M.A. Ausems; David A. Fifield; et al. (Marine Pollution Bulletin, 2026)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Noise results in lower quality of an important forage fish, the Pacific sand lance, Ammodytes personatus - Nora V. Carlson; Meredith A.V. White; Jose Tavera; Patrick D. O'Hara; Matthew R. Baker; Douglas F. Bertram; Adam Summers; David A. Fifield; Francis Juanes (Marine Pollution Bulletin, 2025)

Migratory pathways and winter destinations of Northern Gannets breeding at Helgoland (North Sea): known patterns and increasing importance of the Baltic Sea - Stefan Garthe; Verena Peschko; David A. Fifield; Kai Borkenhagen; Timme Nyegaard; Jochen Dierschke (Journal of Ornithology, 2024)
We analysed the migratory behaviour of adult Northern Gannets ( Morus bassanus ) breeding at Helgoland in the North Sea, based on data obtained from geolocation devices in the non-breeding season 2016–2017. Birds moved east and south-west to a broad range of wintering sites, ranging from the western Baltic Sea to North-West Africa. Three out of 12 birds spent the winter in Africa, while 9 birds wintered in Europe, with the primary wintering sites in the North Sea. All but one tagged bird spent some time in the Baltic Sea or in the transitional waters between the North Sea and Baltic Sea. We also analysed data from online databases (dofbasen.dk, ornitho.de) and the German Seabirds at Sea database to explore the extent to which Northern Gannets used the western Baltic Sea, as well as the Kattegat and Skagerrak, during the winter months. Records of Northern Gannets in Danish waters have increased substantially over the last 18 winters, with particular increases in the Baltic Sea. There was also a notable increase in sightings of Northern Gannets in German Baltic Sea waters, but this occurred later than in the more northerly Danish waters. Both analyses demonstrated that Northern Gannets explored the western part of the Baltic Sea, as well as the Kattegat and Skagerrak, increasingly intensively. This recent increase in sightings is in accord with the establishment and exponential increase in the nearest breeding colony of Northern Gannets at Helgoland.

Inter-colony variation in predation, mercury burden and adult survival in a declining seabird - Anna M. Calvert; Sarah E. Gutowsky; David A. Fifield; Neil M. Burgess; Rachel Bryant; Gail S. Fraser; Carina Gjerdrum; April Hedd; Patricia L. Jones; Robert A. Mauck; Laura McFarlane Tranquilla; William A. Montevecchi; et al. (Science of The Total Environment, 2024)

Predicting Seabird Foraging Habitat for Conservation Planning in Atlantic Canada: Integrating Telemetry and Survey Data Across Thousands of Colonies - Robert A. Ronconi; David J. Lieske; Laura A. McFarlane Tranquilla; Sue Abbott; Karel A. Allard; Brad Allen; Amie L. Black; François Bolduc; Gail K. Davoren; Antony W. Diamond; David A. Fifield; Stefan Garthe; et al. (Frontiers in Marine Science, 2022)
Conservation of mobile organisms is difficult in the absence of detailed information about movement and habitat use. While the miniaturization of tracking devices has eased the collection of such information, it remains logistically and financially difficult to track a wide range of species across a large geographic scale. Predictive distribution models can be used to fill this gap by integrating both telemetry and census data to construct distribution maps and inform conservation goals and planning. We used tracking data from 520 individuals of 14 seabird species in Atlantic Canada to first compare foraging range and distance to shorelines among species across colonies, and then developed tree-based machine-learning models to predict foraging distributions for more than 5000 breeding sites distributed along more than 5000 km of shoreline. Despite large variability in foraging ranges among species, tracking data revealed clusters of species using similar foraging habitats (e.g., nearshore vs. offshore foragers), and within species, foraging range was highly colony-specific. Even with this variability, distance from the nesting colony was an important predictor of distribution for nearly all species, while distance from coastlines and bathymetry (slope and ruggedness) were additional important predictors for some species. Overall, we demonstrated the utility of tree-based machine-learning approach when modeling tracking data to predict distributions at un-sampled colonies. Although tracking and colony data have some shortcomings (e.g., fewer data for some species), where results need to be interpreted with care in some cases, applying methods for modeling breeding season distributions of seabirds allows for broader-scale conservation assessment. The modeled distributions can be used in decisions about planning for offshore recreation and commercial activities and to inform conservation planning at regional scales.

Foraging Paths of Breeding Leach’s Storm-Petrels in Relation to Offshore Oil Platforms, Breeding Stage, and Year - Sydney M. Collins; April Hedd; David A. Fifield; David R. Wilson; William A. Montevecchi (Frontiers in Marine Science, 2022)
The global population of Leach’s Storm-Petrels ( Hydrobates leucorhous ), the smallest and most abundant breeding seabird species in eastern Canada, has declined substantially in recent decades. The species is listed as “Threatened” by the Committee On the Status of Endangered Wildlife in Canada (COSEWIC) and as “Vulnerable” by the International Union for Conservation of Nature (IUCN). Fatal attraction to anthropogenic light is a major risk for Leach’s Storm-Petrels and many other nocturnal seabirds. From May to September each year, Leach’s Storm-Petrels in eastern Canada breed in island colonies and travel many hundreds of kilometers to obtain prey for themselves and their chick. At the species’ largest colonies in eastern Newfoundland, brightly illuminated oil production platforms intersect breeding storm-petrels’ foraging paths. The level of risk posed by these platforms is poorly understood. GPS tracking from 2016 to 2021 at one of the world’s largest colonies revealed considerable similarity in foraging trip distance, location, and behavior (inferred from Hidden Markov Models) among years, and a decrease in trip distance and duration between incubation and chick-rearing. Leach’s Storm-Petrels flew within the light catch-basin of an oil platform in 17.5% of trips, and the birds tended to transit rapidly past platforms during the day when light attraction is minimal. Exposure to oil platforms at night occurred in only 1.1% of trips. Despite our findings, Leach’s Storm-Petrels are known to strand on oil platforms in large numbers, especially during the fledging period. In addition, storm-petrels migrate over great distances and are likely exposed to brightly illuminated oceanic oil platforms outside the breeding season. Our results emphasize the need to focus conservation research on risks during migration and winter, and on juveniles and immature birds.

Small-Scale Patterns in the Distribution and Condition of Bamboo Coral, Keratoisis grayi, in Submarine Canyons on the Grand Banks, Newfoundland - Krista D. Baker; Paul V. R. Snelgrove; David A. Fifield; Evan N. Edinger; Vonda E. Wareham; Richard L. Haedrich; Kent D. Gilkinson (Frontiers in Marine Science, 2019)

Employing Predictive Spatial Models to Inform Conservation Planning for Seabirds in the Labrador Sea - David A. Fifield; April Hedd; Stephanie Avery-Gomm; Gregory J. Robertson; Carina Gjerdrum; Laura McFarlane Tranquilla (Frontiers in Marine Science, 2017)

East or west? Migration routes and wintering sites of Northern Gannets Morus bassanus from south-eastern Iceland - Stefan Garthe; Gunnar T. Hallgrimsson; William A. Montevecchi; David Fifield; Robert W. Furness (Marine Biology, 2016)

Movements and wintering areas of breeding age Thick-billed Murre Uria lomvia from two colonies in Nunavut, Canada - Anthony J. Gaston; Paul A. Smith; Laura McFarlane Tranquilla; William A. Montevecchi; David A. Fifield; H. Grant Gilchrist; April Hedd; Mark L. Mallory; Gregory J. Robertson; Richard A. Phillips (Marine Biology, 2011)